USING SHORT VIDEOS TO IMPROVE 7TH GRADE STUDENTS' VOCABULARY MASTERY - Azis, Astuti; Setianto, Daud (Universitas Terbuka, 2023)
This research focuses on how to improve students’ English vocabulary mastery using short videos. The subject of the research was Class VII-A SMP Pangudi Luhur Santo Yusup Semarang with a total of 24 students. The research was conducted in semester 2 of the 2022/2023 academic year in two cycles. Data was collected using observation techniques and qualitative and quantitative data collection. In pre-cycle activities, less than 50% of students get satisfactory formative test results, and students tend to be passive during the learning process. In cycle 1, there was a change in student scores, more than 60% of students got satisfactory results, and student-teacher engagement also increased. During cycle 2, 80% of students got satisfactory learning outcomes through changes in formative test scores. It can be concluded that the use of video is beneficial to improve students’ mastery of English vocabulary